Detection of plant growth enhancing features in psychrotolerant yeasts from Patagonia (Argentina) - Mestre, María Cecilia (2016)
This study explores the biotechnological potential for plant production of twelve psychrotolerant yeasts strains from Northwest-Patagonia. These strains were isolated from different substrates associated with Nothofagus sp. in native forests and Vaccinium sp. in a commercial plantation. Yeasts characterization was performed using in vitro assays to evaluate the production of auxin-like compounds and siderophores, ability to solubilize inorganic phosphate and to reduce common plant pathogen growth. Strain YF8.3 identified as Aureobasidium pullullans was the main producer of auxin-like and siderophores compounds. Phosphate solubilization was a characteristic observed by strains L8.12 and CRUB1775 identified as Holtermaniella takashimae and Candida maritima, respectively. Different yeast strains were able to inhibit the growth of Verticillium dahliae PPRI5569 and Pythium aphanidermatum PPRI 9009, but they all failed to inhibit the growth of Fusarium oxysporum PPRI5457. The present study, suggests that yeasts present in different environments in Northwestern-Patagonian have physiological in vitro features which may influence plant growth. These results are promising for the developing of biological products based on Patagonian yeasts for plant production in cold-temperate regions.